A general model of international tax competition with applications - Helmuts Azacis; David R. Collie (Cardiff University, Cardiff Business School, 2021)
A general version of the ZMW model of international tax competition is presented that confirms and extends the results of the existing literature about the choice of tax policy instruments in the symmetric case when the tax externality is positive for both countries. In the asymmetric case when the tax externality is positive for one country and negative for the other country, it is shown that the results are reversed. This demonstrates the importance of the sign of the tax externality in models of international ta x competition. This general model is then used to analyse a couple of policy-relevant applications: depreciation allowances and interest payment deductibility.
Keywords: H21; H25; H77; F21; F23; F53; C72; 330; Tax Competition; Proportional Taxes; Per-Unit Taxes; Capital Taxes